Reelin (RELN) DNA methylation in the peripheral blood of schizophrenia - Rahim Mohd, Nabil Fikri; A.Talib, Norlelawati; Abd. Rahim, Nour El Huda; Mohd Noor, Hanisah; Abdullah, Kartini; Ku Zaifah, Norsidah; Abdullah, Nor Zamzila (Elsevier Ireland Ltd, 2017)
The epigenetic changes of RELN that are involved in the development of dopaminergic neurons may fit the developmental theory of schizophrenia. However, evidence regarding the association of RELN DNA methylation with schizophrenia is far from sufficient, as studies have only been conducted on a few limited brain samples. As DNA methylation in the peripheral blood may mirror the changes taking place in the brain, the use of peripheral blood for a DNA methylation study in schizophrenia is feasible due to the scarcity of brain samples. Therefore, the aim of our study was to examine the relationship of DNA methylation levels of RELN promoters with schizophrenia using genomic DNA derived from the peripheral blood of patients with the disorder. The case control studies consisted of 110 schizophrenia participants and 122 healthy controls who had been recruited from the same district. After bisufhite conversion, the methylation levels of the DNA samples were calculated based on their differences of the Cq values assayed using the highly sensitive real-time MethyLight TaqMan® procedure. A significantly higher level of methylation of the RELN promoter was found in patients with schizophrenia compared to controls (p = 0.005) and also in males compared with females (p = 0.004). Subsequently, the RELN expression of the methylated group was 25 fold less than that of the non-methylated group. Based upon the assumption of parallel methylation changes in the brain and peripheral blood, we concluded that RELN DNA methylation might contribute to the pathogenesis of schizophrenia. However, the definite effects of methylation on RELN function during development and also in adult life still require further elaboration.